2019
DOI: 10.2147/dddt.s207425
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and toxicity of cladribine for the treatment of refractory acute myeloid leukemia: a meta-analysis</p>

Abstract: Purpose: To investigate the overall efficacy and toxicity of cladribine and cladribine-based chemotherapy in the treatment of patients with refractory acute myeloid leukemia (AML) based on meta-analysis. Methods: PubMed, EMBASE database, and the Cochrane Library were searched for relevant studies. Eligible studies were clinical trials of refractory AML assigned to cladribine with data on efficacy including complete remission (CR) rate, overall response rate (ORR) and overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The unaffordable prices of traditionally developed compounds combined with an unmet clinical need to improve OS in AML have encouraged the exploration of repurposing as a feasible strategy [ 42 ]. Several examples of drug repurposing in AML have been identified in the literature [ 43 , 44 ]; most often, these arise serendipitously through observed side effects, as evidenced by thalidomide [ 20 ]. More recently, compounds have been identified through the application of high-throughput screening (HTS) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The unaffordable prices of traditionally developed compounds combined with an unmet clinical need to improve OS in AML have encouraged the exploration of repurposing as a feasible strategy [ 42 ]. Several examples of drug repurposing in AML have been identified in the literature [ 43 , 44 ]; most often, these arise serendipitously through observed side effects, as evidenced by thalidomide [ 20 ]. More recently, compounds have been identified through the application of high-throughput screening (HTS) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that pretreatment with cladribine increased the rate of Ara-CTP accumulation in leukemic blasts by 50-65% in in vitro and in vivo pharmacological studies [21]. A recent meta-analysis reported that the CR rate of cladribine used in refractory AML patients was 42.2% (95% CI: 31.0-54.3%), and the ED rate was 6.8% (95% CI: 4.3-10.6%) [22]. To date, there have been reviews report on cladribine-containing regimens used for induction therapy of newly diagnosed AML patients, but these studies only listed the results of clinical trials without statistical analysis and no comparison between different regimens was conducted [3,21].…”
Section: Discussionmentioning
confidence: 99%
“…In the new therapeutic setting, it is used in combination with cytarabine, idarubicin, or both [ 30 ]. Cladribine resulted in being an effective anti-AML therapying in a meta-analysis of 10 clinical trials [ 31 ]. It improves clinical outcomes with no adverse effects when added to standard therapy [ 32 ].…”
Section: Drug Repurposing In Amlmentioning
confidence: 99%